Operation pretense : the FBI's sting on county corruption in Mississippi - Crockett, James R. (University Press of Mississippi, 2003)
During the 1980s fifty-seven of Mississippi's 410 county supervisors from twenty-six of the state's eighty-two counties were charged with corruption. The FBI's ploy to catch the criminals was code-named Operation Pretense. Ingenious undercover investigation exposed the supervisors' wide-scaled subterfuge in purchasing goods and services. Because supervisors themselves controlled and monitored the purchasing system, they could supply sham documentation and spurious invoices. Operation Pretense was devised in response to the complaint of a disgruntled company owner, a Pentecostal preacher who ba.